The Challenge of Sustainable Development : Keynote Address at the World Resources Institute - Preston, Lewis T. (World Bank, Washington, DC, 2019)
Lewis T. Preston, President of the World Bank, reviewed WRI and Bank collaboration to address global poverty issues. The Rio Consensus added impetus to the work on sustainable development, highlighting the environmental problems faced by the world’s poorest people. The World Bank has integrated these concerns into its work, adding environmental assessment for projects financed and supporting national environmental action plans. He concluded that poverty is at the root of both development problems and environmental problems. To protect the environment we must reduce poverty.